Microfinance and the development of small and medium scale enterprises in the Awutu Senya East Municipality in he central region of Ghana - Fiable Patrick (University of Cape Coast, 2025)
Despite the growing availability of microfinance services to support SMEs' growth, many of these businesses still struggle with limited access to adequate capital, high interest rates, poor financial management, and inadequate business infrastructure. The study explained the contribution of microfinance institutions in the development of small and medium scale enterprises (SMEs) in the Awutu Senya East Municipality in the Central region of Ghana. The study employed a cross-sectional design with mixed methods, combining both quantitative and qualitative data collection and analysis. Sampling techniques included cluster, purposive, proportional, and simple random sampling, with a sample of 321 SME operators drawn from a total population of 1648 using Miller and Brewer’s (2003) sample size determination formula, while 33 MFI staff, and 5 MFI managers were purposively sampled for the study. The quantitative analyses were aided by Statistical Package for Social Sciences (SPSS) using varied statistical tools, while qualitative data were analysed using the line-by-line analysis technique proposed by Corbin and Strauss (2008). The findings revealed that the major source of finance to the SMEs was loan from MFIs since that was easier to obtain compared to other means of acquiring capital to start-up businesses. It was found that there were no significant impacts of the independent variables such as savings, access to loan and training on the SMEs business growth. It was concluded that SMEs did personal savings but that was very slow in terms of business expansion so they relied mainly on micro financial institutions for their loan. It is recommended that MFIs should provide loans with flexible loan repayment terms to their clients in order to avoid the case of defaulters.
xiii,152p:,ill
Keywords: Microfinance Development Small and Medium Enterprise